EFEKTIVITAS PEMBELAJARAN PMRI BERBASIS OPEN-ENDED TERHADAP KEMAMPUAN BERPIKIR KRITIS SISWA DI MTSN 1 KOTA KEDIRI - Evi Diana Supraning Ayu; Eka Sulistyawati; Dewi Hamidah (Lentera Sriwijaya : Jurnal Ilmiah Pendidikan Matematika, 2023)
This study aims to determine the effectiveness of PMRI learning with open-ended problems on students' mathematical critical thinking ability in  MTsN 1 Kota Kediri. This research method used a quasi-experimental design with a non-equivalent pretest posttest control group design. The population of this research is all of class VIII MTsN 1 Kota Kediri. Sample of this research are Class VIII G was the experimental group and class VIII E was the control group. The instruments used are test questions (pretest and posttest) based on critical thinking indicators including interpretation, analysis, evaluation, inference, and explanation, RPP and learning implementation observation sheet. The results show that the average pretest and posttest scores of students' critical thinking skills in the open-ended-based PMRI class were 33.8 and 75.79. While the average pretest and posttest classes that use conventional learning are 33.97 and 65.50.The results of the independent sample t-test and obtained the value of sig. (2-tailed) is 0.000 where 0.000 < 0.05 so is accepted. This means that there is a difference in the average critical thinking ability of students after using PMRI learning based on open-ended with conventional learning. Furthermore, to determine the level of effectiveness of the learning model used, the n-gain test was carried out and the average n-gain score for the experimental class was 0.6379, and was categorized as moderate. While the control class is 0.4800 and is categorized as moderate. The average value of the experimental class n-gain score is greater than the control class, so it can be concluded that Open Ended-based PMRI learning is more effective in improving students' critical thinking skills.